(untitled) (Global Journal of Human-Social Science, 2021)
The present work has as presupposition the consideration that the teaching of Proofs and Demonstrations starting from experimental activities can lead the student to develop a higher level of Geometric understanding The empirical data that allowed the construction of this assumption comes from a research conducted by Cabral 2017 with students of the 3rd period of the Degree in Mathematics Considering the complexity of teaching and learning geometric proofs and demonstrations not only for the student but also for the teacher the activity described here Discovering the properties of the Conics with GeoGebra was developed in the sense of proposing teaching situations that lead to the student to observe experiment reflect conjecture and refute The data obtained were analyzed according to the test model proposed by Balacheff 2000 We present in this article some data resulting from the application of this activity in the classroom followed by some related reflections